NIR nanoprobe-facilitated cross-referencing manifestation of local disease biology for dynamic therapeutic response assessment. Issue 3 (6th December 2019) - Wang, Zhimin; Ai, Xiangzhao; Zhang, Zhijun; Wang, Yong; Wu, Xiangyang; Haindl, Richard; Yeow, Edwin K. L.; Drexler, Wolfgang; Gao, Mingyuan; Xing, Bengang
Abstract : NIR photoacoustic and upconversion luminescent nanoprobe-facilitated cross-referencing manifestation of oxidative stress-induced liver pathophysiology for dynamic therapeutic response assessment. Abstract : Pharmacological interventions for effective treatment require opportune, dynamic and accurate manifestation of pathological status. Traditional clinical techniques relying on biopsy-based histological examinations and blood tests are dramatically restricted due to their invasiveness, unsatisfactory precision, non-real-time reporting and risk of complications. Although current strategies through molecular imaging enable non-invasive and spatiotemporal mapping of pathological changes in intact organisms, environment-activatable, sensitive and quantitative sensing platforms, especially for dynamic feedback of the therapeutic response, are still urgently desired in practice. Herein, we innovatively integrate deep-tissue penetrable multispectral optoacoustic tomography (MSOT) and near-infrared (NIR) optical imaging based technology by tailoring a free radical-responsive chromophore with photon-upconverting nanocrystals. During the therapeutic process, the specific reactions between the drug-stimulated reactive oxygen species (ROS) and radical-sensitive probes result in an absorption shift, which can be captured by MSOT. Meanwhile, the radical-triggered reaction also induces multispectral upconversion luminescence (UCL) responses that exhibit the opposite trend in comparison to MSOT. Such reversed-ratiometric dual-modal imaging outcomes provide an ideal cross-referencing system that guarantees the maximum sensing specificity and sensitivity, thus enabling precise disease biology evaluation and treatment assessments in vivo .